(untitled) (Cambridge, 2005)
This compilation of 45 case studies documents disparate experiences among economies in addressing the challenges of participating in the WTO. It demonstrates that success or failure is strongly influenced by how governments and private sector stakeholders organise themselves at home
Keywords: International trade,International trade,Thương mại quốc tế